(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the article East of thinker’s education, manners issues views about the word held. Also East of thinkers creative in the activity to education about approaches, ideas, views young generation to his mind in absorption education methods and tools awareness in life of them to gray use pedagogue k education in the process of the pedagogue skill important from the features one the fact that light up given.